Friday

August 29, 2014

August 29, 2014

Posted by **Kendall** on Saturday, August 2, 2008 at 6:52pm.

f(0)=

f(-1)=

f(2)=

- Math -
**drwls**, Saturday, August 2, 2008 at 7:54pmJust plug in the numbers in parentheses () for x and perform the calculation.

For example,

f(0) = 5*0^2 - 2*0 = 0

Now you should be able to do the other two.

**Related Questions**

math - find the indicated outputs for f(x)=3x^2-4x f(0)= f(-1)= f(2)=

Math - Find the indicated outputs for f(x)= 5x^2-5x. F(0) = 0 f(-1)= 1 f(2)= 45 ...

math - Function k(x) = x+18 Find k(0) k(x) = 6x k(-2) k(5) k(-2) indicated ...

Math - Find the indicated outputs for f(x)= 5x^2-2x The 2 after the ^ is an ...

math - can someone help me I am not understandng how to do this; Function k(x...

math - can someone check this please find indicated outputs for f(x)= 4x^2 - 2x ...

Algebra - Find the indicated outputs for f(x)=¡¼5x¡½^(2 )-2x f(0)= f(-1)= f(2)=

algebra - Find the indicated outputs for f(x) =4x^2 -4x f(0) f(-1) f(2)

algebra - Find the indicated outputs for f(x)=4x^2 -4x f(0) f(-1) f(2)

algebra - find the indicated outputs for f(x)5^2-4x F(0)= f(-1)= f(2)=